The Structure and Conformation of (CH3)3CSNO - Canneva, Antonela (2015)
The gas-phase molecular structure of (CH3)3CSNO was investigated by using electron diffraction, allowing the first experimental geometrical parameters for an S-nitrosothiol species to be elucidated. Depending on the orientation of the SNO group, two conformers (anti and syn) are identified in the vapor of (CH3)3CSNO at room temperature, the syn conformer being less abundant. The conformational landscape is further scrutinized by using vibrational spectroscopy techniques, including gas-phase and matrix-isolation IR spectroscopy, resulting in a contribution of ca. 80:20 for the anti:syn abundance ratio, in good agreement with the computed value at the MP2(full)/cc-pVTZ level of approximation. The UV/Vis and resonance Raman spectra also show the occurrence of the conformational equilibrium in the liquid phase, with a moderate post-resonance Raman signature associated with the 350 nm electronic absorption.